Pengaruh Kualitas Produk Dan Costumer Review Terhadap Keputusan Pembelian Di Lazada - Putri, Viki Anjani; Prabowo, Heri; Setyorini, Noni (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2024)
This study aims to analyze the effect of product quality variables, customer reviews, and service quality on purchasing decisions at Lazada. With a case study studied on consumers who shop at the Lazada application in Srondol Kulon Village, Banyumanik District, Semarang City. The research method in this research is a quantitative approach. The population in this study were all buyers on the Lazada Application in Srondol Kulon Village, Banyumanik District, Semarang City, while the sample taken in this study was 100 Lazada Application users. Determination of the sample size using the method of non-proprability sampling technique and selection of respondents with purposive sampling technique. Data analysis in this study using the SmartPLS version 3 program. The data analysis technique used is the Structural Equation Modeling (SEM) equation model. From the results of the analysis and discussion of this study, it shows that the product quality variable has a significant influence on purchasing decisions, the customer review variable does not have a significant influence on purchasing decisions, and the service quality variable has a significant influence on purchasing decisions.